Characterization of Amphetamine, Methylphenidate, Nicotine, and Atomoxetine on Measures of Attention, Impulsive Action, and Motivation in the Rat: Implications for Translational Research - Higgins, Guy A.; Silenieks, Leo B.; MacMillan, Cam; Thevarkunnel, Sandy; Parachikova, Anna I.; Mombereau, Cedric; Lindgren, Hanna; Bastlund, Jesper F. (Frontiers in Pharmacology, 2020)
Amphetamine (AMP), methylphenidate (MPH) and atomoxetine (ATX) are approved treatments for ADHD, and together with nicotine (NIC) represent pharmacological agents widely studied on cognitive domains including attention and impulsive action in humans. These agents thus represent opportunities for clinical observation to be reinvestigated in the preclinical setting, i.e. reverse translation. The present study investigated each drug in male, Long Evans rats trained to perform either (1) the 5-choice serial reaction time task (5-CSRTT), (2) Go/NoGo task, or (3) a progressive ratio task, for the purpose of studying each drug on attention, impulsive action and motivation. Specific challenges were adopted in the 5-CSRTT designed to tax attention and impulsivity, i.e. high frequency of stimulus presentation (sITI), variable reduction in stimulus duration (sSD), and extended delay to stimulus presentation (10s ITI). Initially performance of a large (>80) cohort of rats in each task variant was conducted to examine performance stability over repeated challenge sessions, and to identify subgroups of “high” and “low” attentive rats (sITI and sSD schedules), and “high” and “low” impulsives (10s ITI). Using an adaptive sequential study design, the effects of AMP, MPH, ATX and NIC were examined and contrasting profiles noted across the tests. Both AMP (0.03-0.3mg/kg) and MPH (1-6mg/kg) improved attentional performance in the sITI but not sSD or 10s ITI condition, NIC (0.05-0.2mg/kg) improved accuracy across all conditions. ATX (0.1-1mg/kg) detrimentally affected performance in the sITI and sSD condition, notably in “high” performers. In tests of impulsive action, ATX reduced premature responses notably in the 10s ITI condition, and also reduced false alarms in Go/NoGo. Both AMP and NIC increased premature responses in all task variants, although AMP reduced false alarms highlighting differences between these two measures of impulsive action. The effect of MPH was mixed and appeared baseline dependent. ATX reduced break point for food reinforcement suggesting a detrimental effect on motivation for primary reward. Taken together these studies highlight differences between AMP, MPH and ATX which may translate to their clinical profiles. NIC had the most reliable effect on attentional accuracy, while ATX was reliably effective against all models of impulsive action.